Pendampingan Pelatihan Pembuatan Video Pembelajaran bagi Visual Kinesthetic Learner untuk Guru di Sekolah Menengah Atas Kota Jayapura - Onnie Lumintang; Salahudin Salahudin (Fakultas Teknik Universitas Cenderawasih, 2022)
Training on making learning videos for teachers in Jayapura City High School aims to improve teachers' ability to teach students with visual kinesthetic learning type. The research used a qualitative approach and hands-on training method. The results show that the use of videos as learning media can increase student interest and understanding, as well as provide a more interactive learning experience. Ultimately, this training is expected to contribute to the quality of education in the Jayapura City area.